AZYGOS VEIN ANEURYSM — RARE IMAGING FINDING. TO TREAT OR NOT TO TREAT? - Coelho, Andreia (2017)
True aneurismal dilatation of the azygos vein is a rare entity which has been reported in the literature on only a few occasions. We report a case of azygos vein aneurysm dilatation that was incidentally discovered on a computed tomography angiogram (CTA), during imagiologic study for hemoptyses, on an anticoagulated female 82 year-old patient. A repeat CTA after one month revealed complete thrombosis of the aneurysm. She was managed conservatively with outpatient follow-up.